Leadership Styles: A Study Of Australian And Thai Public Sectors - Pimpa, Nattavud; Moore, Timothy (Asian Academy of Management (AAM), 2012)
Leadership is deeply attached to culture. This study compares leadership styles in Thai and Australian public sectors. The data were collected from staff in public sector settings in Australia and Thailand. The results confirm four leadership styles that suit the public sector culture in both countries: communication-oriented, strategic thinking and planning, relationship building, and conflict management. In the Thai public sector system, leadership that focuses on goal orientation is ranked most highly: Australian public sector organisations focus on leadership that fosters equity among organisational members, creates a supportive environment in the workplace, and facilitates participation. It is evident from this study that significant distinctions between the organisational cultures of Thailand and Australia are matched by marked dissimilarities of preferred leadership styles. Thus, an understanding of local organisational culture is important for effective leadership at all levels